The association between the use of dry cow therapy and bacteriological cure after calving and the development of phenotypic antimicrobial resistance on Egyptian dairy farms - Wagdy R. ElAshmawy; Noha M. Bakry; Samah M. El-Sayed; Karima M. Fahim; Samira H. Aljuaydi; Huda O. AbuBakr; Adel A. Fayed; Rehab Elhelw; Sharif S. Aly; Heba S. Farag (PLoS ONE, 2026)
Blanket dry cow therapy is a common practice on dairies to control mastitis, and when adopted, constitutes the majority of antimicrobial use on a dairy. The current study aimed to investigate the effect of dry cow therapy on the bacteriological cure and new infections after calving, and the association between dry cow therapy and antimicrobial resistance of Staphylococcus aureus isolated from milk samples of dairy cows after calving on Egyptian dairy farms. A randomized clinical trial was implemented on two Egyptian dairy farms. A total of 400 cows were randomized to one of four intramammary treatments at dry-off (Antibiotic, AB; Internal teat sealant, ITS; AB&ITS, or no treatment; Control). Composite milk samples were collected from enrolled cows at dry-off before receiving treatments and after calving. Bacterial culture and species identification were performed based on colony morphology, biochemical identification, and PCR using 16S rRNA. The Minimum Inhibitory Concentration (MIC) for each of the study Staphylococcus aureus ( S. aureus ) isolates was estimated using a commercial plate (CMV1AMAF Sensititre plate). Logistic regression models were used to estimate the effect of the different dry cow treatments on bacteriological cure and new infections. Parametric survival interval regression models were used to model the association between dry cow treatment and antimicrobial resistance after calving. Cows with a history of mastitis at the dry-off lactation had significantly higher odds (Odds Ratio, OR = 2.2, SE = 0.005, P < 0.01) of bacteriological cure compared to cows with no history of mastitis at the dry-off lactation. The highest percentage of resistance at dry-off was observed against penicillin (64%), sulfadimethoxine (54%), and erythromycin (30%) during the Spring/Summer season, while 37% was observed against penicillin and 30% for sulfadimethoxine during the Fall/Winter season. There was a significant increase in the MIC for ampicillin and ceftiofur in S. aureus isolated from cows that received AB and AB&ITS at dry-off in both study seasons. The current study revealed that more than 30% of subclinical mastitis cows were infected with S. aureus at dry-off and after calving, which requires future studies to evaluate the control measures of contagious mastitis implemented on Egyptian dairies before implementing the selective dry cow therapy algorithm.